ANALISIS PENJADWALAN PREVENTIVE MAINTENANCE MESIN KNEADER PADA PROSES PRODUKSI RUBBER FENDER: Studi Kasus: PT. SEKAR WANGI GROUP, Sidoarjo - Muhammad Riki; Hery Murnawan (LPPM Universitas Bina Bangsa, 2023)
PT. Sekar Wangi Groub is a manufacturing company engaged in the production of rubber products. PT. Sekar Wangi Groub is located on Jl. Ketapang - Suko No.34, Suko Hamlet, Sidoarjo Regency, East Java. Products produced by PT. Sekar Wangi Group is Rubber Fender, Elastomeric bearing pad and Rubber Roll. Activities in the company all use machine tools that operate non-stop during working hours, this is able to make the machine experience a decrease in performance, so that at certain time it will make the machine experience trobel. Therefore, efforts to avoid machine trobel or breakdown can be done by scheduling machine maintenance, routine maintenance on the machine can be done by applying the use of the Preventive maintenance method to make the engine life longer and avoid downtime, with regular maintenance and maintenance on the machine, it is expected to increase production and avoid breakdown in the machine. The result obtained is that the cost of machine maintenance using preventive maintenance results in a smaller total maintenance cost of Rp.7.100.000,- per year compared to the previous breakdown maintenance costs which reached Rp.12.070.741, - the total cost expenditure is smaller if implementing preventive maintenance so that this method is appropriately used by the company.